2019
DOI: 10.3390/su11164425
|View full text |Cite
|
Sign up to set email alerts
|

Predicting First-Year College Student Retention: Validation of the College Persistence Questionnaire in a Spanish Sample

Abstract: This paper analyzes the factorial and predictive validity of a Spanish adaptation of the College Persistence Questionnaire (SCPQ) on the retention of first year students (FYS) at university. The participants were 490 FYS from two public universities in Southern Europe (Spain). Factorial analysis of the SCPQ (χ2/gl = 1.66, CFI = 0.92, NNFI = 0.91, RMSEA = 0.04) showed six reliable dimensions, similar to those found in the original study: Academic Integration, Social Integration, Supportive Services Satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…More specifically, similar to what previous research with first-year engineering students highlights [2,7,10,[57][58][59], no significant differences are observed between males and females in their performance in graphic expression, and there is even a tendency for females to achieve higher results than males. On the other hand, contrary to what various review studies and the working hypotheses [37] suggest, no significant relationship is found between participants' gender and their spatial abilities.…”
Section: Discussionsupporting
confidence: 84%
“…More specifically, similar to what previous research with first-year engineering students highlights [2,7,10,[57][58][59], no significant differences are observed between males and females in their performance in graphic expression, and there is even a tendency for females to achieve higher results than males. On the other hand, contrary to what various review studies and the working hypotheses [37] suggest, no significant relationship is found between participants' gender and their spatial abilities.…”
Section: Discussionsupporting
confidence: 84%
“…As Schonhaut et al [18] affirmed, language difficulties may be associated with learning difficulties and behavioral disorders, which can have an impact on a smaller repertoire of social skills and the aforementioned school problems. For these reasons, it will be interesting to introduce language teaching methodologies specifically adapted to the needs of boys and girls with different educational needs and delays in language acquisition at school, creating educational environments that promote student learning and socio-personal development [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents with an attachment and commitment to school, as well as a higher degree of acceptance of the rules, are less likely to engage in nonadaptive activities than those with weak ties [16]. Researchers such as Aparisi et al [21] aimed to work with teachers and administrations to create educational environments that facilitate learning by promoting the socio-personal development of students [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The present study administered a survey that adopted five factors from the College Persistence Questionnaire (CPQ) developed by Davidson et al (2009). CPQ is a valid, reliable, and well-established validated instrument (Davidson et al, 2009; García-Ros et al, 2019). The survey was offered in English and Korean to allow participants to respond in a preferred language, accounting for the role of language (Sha & Gabel, 2020).…”
Section: Methodsmentioning
confidence: 99%